Efeito de teleconexões climáticas na variabilidade espaço-temporal dos índices de disponibilidade hídrica em uma bacia hidrográfica sob transição climática (Tropical/Semiárido) - Alves, Alberonaldo Lima (2016)
The water availability is the amount of flow that can be used by the society for its development. Various types of use depend on this portion, for example, minimum conditions for dilution of effluent, ecosystem sustainability, irrigation, water supply, power generation, among others. As other hydrological variables, water availability varies in space and time, including by climatic influence. Studies show that climate teleconnection cause hydrological anomalies in different parts of the earth. In these studies, climate indices have been more used, as they allow a better understanding of the physical relationships between atmospheric and hydrological systems. Though some studies have assessed the climate influence on hydrology, there is no literature an assessment of climate effects on the levels of water availability. In this context, this study, we chose to evaluate the effects of climate through its teleconnection the spatiotemporal variability of water availability rates in a watershed in climate transition (semiarid/tropical). As the object of study was chosen the Mundaú River Basin (MRB), located in the Northeast of Brazil. For estimation of availability indices (Q7, Q90 and Q95) hydrologic modeling rainfall- runoff for gap filling and series extension was used. The calibration of the hydrological model the Nash-Sutcliffe coefficient ranged between 0.84 and 0.86 because validation ranged between 0.75 and 0.81. After calibration and validation sets was possible to extend for a period of 48 years (1963-2010) and estimate the levels of availability. Next, were assessed significant correlations by Spearman and Wavelets, considering a 95% confidence interval between the availability indices and climatic indices: North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), Pacific Decadal Oscillation (PDO) and Southern Oscillation Index (SOI). It was found that the spatio-temporal variability of water availability, can be explained by phenomena active in climate transition region (semiarid/hot and humid tropical). In some cases, the climate performance was similar to other not. In addition, the combination of events La Niña and El Niño with AMO and PDO phenomena can influence more strongly the variability of water availability. It stands out in detail that all significant effects of climate on availability, leading or included wet period from March to August (70% of the annual precipitation), very influential period in storage.